Enhanced ambient stability of exfoliated black phosphorus by passivation with nickel nanoparticles. (27th April 2020) - Caporali, Maria; Serrano-Ruiz, Manuel; Telesio, Francesca; Heun, Stefan; Verdini, Alberto; Cossaro, Albano; Dalmiglio, Matteo; Goldoni, Andrea; Peruzzini, Maurizio
Abstract: Since its discovery, the environmental instability of exfoliated black phosphorus (2D bP) has emerged as a challenge that hampers its wide application in chemistry, physics, and materials science. Many studies have been carried out to overcome this drawback. Here we show a relevant enhancement of ambient stability in few-layer bP decorated with nickel nanoparticles as compared to pristine bP. In detail, the behavior of the Ni-functionalized material exposed to ambient conditions in the dark is accurately studied by Transmission Electron Microscopy (TEM), Raman Spectroscopy, and high resolution x-ray Photoemission and Absorption Spectroscopy. These techniques provide a morphological and quantitative insight of the oxidation process taking place at the surface of the bP flakes. In the presence of Ni nanoparticles (NPs), the decay time of 2D bP to phosphorus oxides is more than three time slower compared to pristine bP, demonstrating an improved structural stability within 20 months of observation.